Pengaruh Promosi, Kemudahan Dan Keamanan Terhadap Keputusan Menggunakan Gopay Pada Generasi Z Di Kota Bengkulu - Lutfia, Anisya Lutfia; Hidayati, Arifah; Syofian, Syofian (Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine the influence of promotion, convenience and security on the decision to use Gopay among generation Z in the city of Bengkulu. The nature of this research is associative. The type of data used in this research is quantitative data. The population generation Z from Bengkulu City who have used GoPay at least twice in the last 6 months, totaling 518,189 people. The number of samples set was 100 people. In the data collection process, researchers used the questionnaire method. The method used to analyze the data in this research is a data processing program or data software, namely SPSS version 25. The results of the research state that promotion has a positive and significant effect on the decision to use as evidenced by the t-count value for the promotion variable of 3.216 > t-table of 0.676 and the sig value is 0.002 < 0.05, which means that if promotion increased, will increase. Convenience positive and significant effect on the decision as evidenced by the t-count value for the promotion variable of 3.303>t-table of 0.676 and a sig value of 0.000<0.05 which means that if convenience is further increased, the decision increase. Security has a positive and significant effect evidenced by the t-count value for the promotion variable of 5.274>t-table of 0.676 and a sig value of 0.000<0.05 which means if security is further improved, the decision to use will increase. Together Promotion, Convenience and Security have a positive and significant influence on the Decision to evidenced by the Fcount > Ftable value of 227.219 > 3.94 with a significance of 0.000 < 0.05, with this the Fcount value is greater than Ftable and the significance is below 0.05, which means that if promotion, convenience and security are improved simultaneously, then the decision to use will increase.